Assessment of the Prevalence of Leptospiroses and Hemorrhagic Fever with Renal Syndrome in the Leningrad Region - E. G. Riabiko; D. I. Grechishkina; R. R. Baimova; I. A. Karmokov; L. V. Buts; E. S. Khalilov; I. S. Lyzenko; N. K. Tokarevich (Проблемы особо опасных инфекций, 2024)
The aim of the study was to determine the prevalence of leptospiroses and hemorrhagic fever with renal syndrome (HFRS) among residents of some administrative districts of the Leningrad Region. Materials and methods. 958 blood serum samples of conventionally healthy individuals living in the following territories of the Leningrad Region: Boksitogorsky, Volosovsky, Vyborgsky, Kingiseppsky, Lodeynopolsky, Luzhsky, Podporozhsky, Priozersky, Slantsevsky and Tikhvinsky districts – were analyzed by enzyme immunoassay. The retrospective epidemiological analysis of the incidence of leptospirosis and HFRS in the population of the Leningrad Region in 2011–2020 was carried out based on the data from the Rospotrebnadzor Administration and Forms No. 2 “Information on infectious and parasitic diseases”. Results and discussion. All in all, 54 cases of leptospirosis and 104 cases of HFRS were registered in the Leningrad Region in 2011–2020. The long-term average annual incidence rate (LTAAIR) for leptospirosis was 0.32. In Boksitogorsky, Vyborgsky, Lodeynopolsky, Podporozhsky and Slantsevsky districts, cases of leptospirosis were not recorded, but IgG-antibodies to Leptospira interrogans were detected in residents of those areas. The LTAAIR for HFRS was 0.63. There are no registered cases of HFRS in the Kingiseppsky, Podporozhsky, and Slantsevsky districts. IgG-antibodies to Orthohantavirus were detected in volunteers in all surveyed areas. The detection of specific antibodies in the blood sera of conventionally healthy people living in the Leningrad Region indicates contact of the population with pathogens of leptospirosis and HFRS. The lack of registered morbidity in some areas is probably due to their hypo-diagnosis, as evidenced by the detection of antibodies to the pathogens of these infections in people living in the corresponding territories.